Impact of the Anomalous Latent Heat Flux Over the Kuroshio Extension on Western North American Rainfall in Spring: Interannual Variation and Mechanism - Long, Jingchao; Liu, Chunlei; Liu, Zifeng; Xu, Jianjun (Frontiers in Earth Science, 2021)
The Kuroshio and its extension (KE) significantly influences regional climate through meridional heat transport from the tropical ocean. In this study, the observational data and reanalysis data sets are used to investigate the impact of the latent heat flux (LHF) over the KE region on downstream rainfall and its underlying mechanism. The result shows a “seesaw” structure in rainfall anomaly, dominating the western Canada and the southwestern North America with a correlation coefficient at 0.77 between the two modes. In strong LHF years, strengthened LHF favors to enhance precipitation in the western Canada and reduce that in the southwestern North America. This is primarily associated with an anomalous cyclonic circulation over the KE region, which enhances southwesterly, precipitation and latent heating in the middle troposphere. The heating excites an anomalous cyclonic circulation to its west and an anticyclonic circulation to its east, helping to reinforce the existing anomalous cyclonic circulation in turn and form a positive feedback. The conditions associated with La Niña events favor to above processes. To the upper troposphere, the deepened anomalous cyclonic circulation due to enhanced eddy activities and atmospheric baroclinic instability over the KE strengthens subtropical westerly jet stream and thereby extending eastward on the 200 hPa level. Correspondingly, an elongated zonally lower level cyclonic circulation anomaly across the North Pacific leads to a moisture convergence in the western Canada, which is mainly resulted from the anomalous positive vorticity advection over the left side of exit region of jet stream. The opposite circumstance occurs in weak LHF years presenting an opposed anomalous circulation and rainfall pattern.